Integration of Medical Education and Healthcare Services from an International Perspective - Narges Tabrizchi; Mohammad Ali Mohagheghi (Strides in Development of Medical Education)
Background: An integrated health system is a method to establish more efficient and effective healthcare by prioritizing patients and better meeting the health needs of communities.Objectives: The aim of this article is to present Iran’s experience with integration and examine whether other countries are adopting a similar approach.Methods: A search was conducted in national and international databases using Farsi and English keywords, without any time limit. Official websites of international organizations, health systems, and well-known universities were also searched. Extracted information was analyzed and organized according to the research goals.Results: There are three general interpretations of the term "integration" in the field of health and medical sciences: "Integration in medical education or integrated curriculum," "Integrated care," and "The integration of medical education and healthcare services." Sub-groups are discussed within each topic, and examples and key points are provided. The Iranian health system is presented as an example of integrated medical education and healthcare provision. In addition, the views of the World Health Organization and the World Federation of Medical Education on this approach are briefly reviewed. Similarities were observed between integrated medical education and healthcare provision, integration in medical education, integrated care, and University Health Systems in terms of addressing community health needs and improving the quality of clinical practice.Conclusion: The review showed that while integration is essential for addressing societal health needs and is recommended by international organizations, accountability cannot be achieved solely through curriculum or health service provision integration. Successful integration relies on strong partnerships, effective mentoring, interdisciplinary education, and a commitment to continuous quality improvement. Establishing a dedicated ministry for medical education could align community health needs with training and foster interdisciplinary collaboration. The Iranian health system model has successfully linked education with practice, enhancing health outcomes, especially in rural and underserved regions.